Research progress on the interaction between glucose metabolic reprogramming and lactylation in tumors - Yang, Yi; Wu, Yi; Chen, Hui; Xu, Zehai; Lu, Ruisi; Zhang, Sijie; Zhan, Rui; Xi, Qinghua; Jin, Yunfeng (Frontiers in Immunology, 2025)
Glucose metabolic reprogramming describes the alterations in intracellular metabolic pathways in response to variations in the body’s internal environment. This metabolic reprogramming has been the subject of extensive research. The primary function is to enhance glycolysis for rapid ATP production, even with sufficient oxygen, leading to a significant accumulation of lactic acid, which subsequently affects the functions of tumor cells and immune cells within TME. Lactylation represents a newly identified post-translational modification (PTM) that occurs due to lactate accumulation and is observed in various proteins, encompassing both histone and non-histone types. Lactylation alters the spatial configuration of proteins, influences gene transcription, and thereby regulates gene expression. This modification serves as a significant epigenetic regulatory factor in numerous diseases. Glucose metabolic reprogramming and lactylation are intricately linked in the process of tumorigenesis. Glucose reprogramming activates essential enzymes, including hexokinase 2 (HK2), pyruvate kinase M2 (PKM2), and lactate dehydrogenase A (LDHA), through transcription factors such as HIF-1α and c-Myc, thereby enhancing glycolysis and lactate accumulation. Lactate functions as a metabolite and signaling molecule, acting as a substrate for lactylation facilitated by histone acetyltransferases such as CBP/p300. This epigenetic modification inhibits antitumor immunity through the upregulation of oncogenic signaling pathways, the induction of M2-type macrophage polarization, and the dysfunction of T-cells. Glucose metabolic reprogramming not only influences lactate synthesis but also provides sufficient substrates for lactate modification. The two factors jointly affect gene expression and protein function, acidify the tumor microenvironment, regulate immune evasion, and promote carcinogenesis. This review systematically details the mechanisms of lactylation and glucose metabolic reprogramming, their impacts on immune cells within the tumor microenvironment, and their interrelations in tumor progression, immunity, and inflammation.